N-3 PUFAs induce inflammatory tolerance by formation of KEAP1-containing SQSTM1/p62-bodies and activation of NFE2L2. Issue 10 (3rd October 2017) - Mildenberger, Jennifer; Johansson, Ida; Sergin, Ismail; Kjøbli, Eli; Damås, Jan Kristian; Razani, Babak; Flo, Trude Helen; Bjørkøy, Geir
ABSTRACT: Inflammation is crucial in the defense against infections but must be tightly controlled to limit detrimental hyperactivation. Our diet influences inflammatory processes and omega-3 polyunsaturated fatty acids (n-3 PUFAs) have known anti-inflammatory effects. The balance of pro- and anti-inflammatory processes is coordinated by macrophages and macroautophagy/autophagy has recently emerged as a cellular process that dampens inflammation. Here we report that the n-3 PUFA docosahexaenoic acid (DHA) transiently induces cytosolic speckles of the autophagic receptor SQSTM1/p62 (sequestosome 1) (described as SQSTM1/p62-bodies) in macrophages. We suggest that the formation of SQSTM1/p62-bodies represents a fast mechanism of NFE2L2/Nrf2 (nuclear factor, erythroid 2 like 2) activation by recruitment of KEAP1 (kelch like ECH associated protein 1). Further, the autophagy receptor TAX1BP1 (Tax1 binding protein 1) and ubiquitin-editing enzyme TNFAIP3/A20 (TNF α induced protein 3) could be identified in DHA-induced SQSTM1/p62-bodies. Simultaneously, DHA strongly dampened the induction of pro-inflammatory genes including CXCL10 (C-X-C motif chemokine ligand 10) and we suggest that formation of SQSTM1/p62-bodies and activation of NFE2L2 leads to tolerance towards selective inflammatory stimuli. Finally, reduced CXCL10 levels were related to the improved clinical outcome in n-3 PUFA-supplemented heart-transplant patients and we propose CXCL10 as a robust marker for the clinical benefits mobilized by n-3 PUFA supplementation.